Sustainable Development in the European Union and World Economy-Main Selected Aspects - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of the paper is to present key theoretical and empirical issues of sustainable development and environmental protection issues from the global and European perspective, with special reference to the implication of this concept for Central and Eastern European members of the EU. Main aspects are discussed in the paper from the EU and global perspective, with special reference to: the global partnership for sustainable development; fighting poverty and promoting social development; sustainable management of natural and environmental resources; trading in greenhouse gas emission allowances; main global and European challenges; goals and challenges facing the European Union member states as stemming from major strategic European Union renewed documents promoting sustainable development; especially promoting consumption and production that is sustainable and environmentally-friendly and green labeling system; a detailed look at "new" environmental policies; with special reference to sustainable transportation; a strategy for the sustainable use of natural resources; preventive strategy (preventing the creation of wastes) and waste recycling; sustainable and competitive tourism.